2023
DOI: 10.3390/diagnostics13213386
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Phase Duration in Robot-Assisted Partial Nephrectomy: A Surgical Data Science Exploration for Clinical Relevance

Pieter De Backer,
Maria Peraire Lores,
Meret Demuynck
et al.

Abstract: (1) Background: Surgical phases form the basic building blocks for surgical skill assessment, feedback, and teaching. The phase duration itself and its correlation with clinical parameters at diagnosis have not yet been investigated. Novel commercial platforms provide phase indications but have not been assessed for accuracy yet. (2) Methods: We assessed 100 robot-assisted partial nephrectomy videos for phase durations based on previously defined proficiency metrics. We developed an annotation framework and su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous studies have assessed the importance of SVR as De Backer et al [3] did for 100 RPNs and showed that surgical phase duration can be correlated with certain clinical outcomes. They found BMI and the duration of renal tumour identification to positively correlate, as higher BMI involves often more intraabdominal fatty tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed the importance of SVR as De Backer et al [3] did for 100 RPNs and showed that surgical phase duration can be correlated with certain clinical outcomes. They found BMI and the duration of renal tumour identification to positively correlate, as higher BMI involves often more intraabdominal fatty tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical video review (SVR) is an emerging tool for assessing patient outcomes [3], especially in complex surgeries such as robot-assisted partial nephrectomy (RAPN). Robotic surgery platforms enable high-quality video recordings, providing greater magnification and closer views of anatomical details.…”
Section: Introductionmentioning
confidence: 99%
“…I n recent years, minimally invasive surgery (MIS) video has become central to enabling live streaming, telementoring, post hoc case evaluation, skill assessment, and novel technological advancements through artificial intelligence (AI), virtual reality, and robotic automation. 1,2 On a legal or ethical basis, video anonymization is essential for sharing data across institutions. 3,4 This anonymization is currently limited to manually removing patient metadata, including names and other identifiable information, such as data and recording locations from file names only.…”
mentioning
confidence: 99%
“…Furthermore, the advent of AI for surgical video analysis requires anonymized video sharing with technical people who have no role in the patient-physician relationship. From an AI-engineering perspective, automated anonymization is required, as it facilitates the creation of large and varied data sets, it is a preprocessing step for AI-assisted video analysis, 2,8 and it speeds up the labeling efforts for supervised AI techniques. 9 Manual video processing, including out-of-body image reviews, is time-consuming and prone to human error.…”
mentioning
confidence: 99%
See 1 more Smart Citation